The Influence of Cloud Computing Services in GATS’ Enforcement - Eugenia Patricia Novoa Zubirria (Foro, Revista de Derecho)
Cloud computing facilities have a cross-border scope that might set off international issues regarding different areas of law. As cloud computing raised from the idea of replacing the physical for the virtual, we must remain that every software needs hardware to operate, whether the second is imperceptible for cloud services’ users, and this makes the cloud of cross border nature. Cloud computing has tangible effects on enterprises and economics, and its characteristics enforce internet usage globally. Explicitly, this article will focus on the influence of cloud computing in an international trade system held by Word Trade Organization (WTO), and how it enforces the international trade system, specifically on the General Agreement of Trade and Services (GATS). This paper main objective is to understand how can cloud computing lead to the enforcement of the international trade system, specifically on the GATS. To address this question, the paper follows an economic analysis of the law with qualitative method of literature and case law analysis, particularly of WTO Us Gamblin. The key conclusion is that the cross-border nature of cloud computing services requires to create a new category in the WTO GATS.